Primary electron transfer kinetics in bacterial reaction centers with modified bacteriochlorophylls at the monomeric sites BA,B. - Finkele, U (1992)
The primary electron transfer has been investigated by femtosecond time-resolved absorption spectroscopy in two chemically modified reaction centers (RC) of Rhodobacter sphaeroides, in which the monomeric bacteriochlorophylls BA and BB have both been exchanged by 13(2)-hydroxybacteriochlorophyll a or [3-vinyl]-13(2)-hydroxybacteriochlorophyll a. The kinetics of the primary electron transfer are not influenced by the 13(2)-hydroxy modification. In RCs containing [3-vinyl]-13(2)-hydroxybacteriochlorophyll a the primary rate is reduced by a factor of 10.